THE INCLUSION OF LGBTQIA+ UNIVERSITY STUDENTS ON CAMPUS: SOME PRACTICAL ASPECTS - BULBOACĂ Gabriel (EcoSoEn: Ştiinţe Economice, Sociale şi Inginereşti = Economics, Social and Engineering Sciences)
This paper addresses some conceptual and practical aspects related to campus inclusion of university students who publicly disclose their gender identity and/or sexual orientation. Across the world, harassment, discrimination and exclusion of LGBTQIA+ students is a sensitive issue. Such undesirable attitudes are based on prejudice and stigma that are rooted in cultural beliefs about traditional gender roles, masculinity and femininity, as well as heterosexism. Harassment and discrimination of students based on sexual orientation and/or gender identity and expression negatively affect their physical and mental health, as well as their efforts to adapt to the demands of academic life. By invoking the universal rights of the human individual, various international organizations (e.g., the United Nations or European Commission) have requested members to adopt an integrated set of measures to sanction and prevent psychological harassment, discrimination and university exclusion of LGBTQIA+ students. There is a need to increase public awareness of the rights of this vulnerable group of students. They can be provided with psychological, social, legal and academic support in various forms. Some measures focused on the inclusion of LGBTQIA+ students on the university campus are presented.